Diagnostics and Prognostics of Electric Cables in Ship Power Systems via Joint Time-Frequency Domain Reflectometry - Jingjiang Wang; Crapse, P.; Yong-June Shin; Dougal, R. (2008 IEEE Instrumentation and Measurement Technology Conference, 2008)
The integrity of the wiring in the electric power system of a ship is vital to its safe operation. To ensure the wiring integrity, it must be tested to determine if any incipient defects exist. Due to this problem, a non-destructive, non-intrusive condition assessment technique is highly desirable. Joint time-frequency domain reflectometry (JTFDR) is proposed and the theory behind JTFDR is also discussed. The experimental results demonstrate and verify the ability of JTFDR to be effective for polytetrafluoroethylene (PTFE) coaxial cable, which has been widely adopted for military applications in ship power systems. It is shown that JTFDR has the ability to detect and locate incipient defects with high accuracy and monitor the aging process of the cables to predict both future defects and the remaining service life of the cables.